DETERMINAN KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2018-2019 - Natikhoh, Yunah; Chomsatu Samrotun, Yuli (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Timeliness of the submission of financial statements is a condition in which the auditedfinancial statements are submitted on time according to a predetermined time limitbefore losing meaning by users of financial statements and their capacity is stillavailable for decision making. This study was conducted to examine and analyze theeffect of profitability, company size, company age, and auditor reputation on thetimeliness of financial report submission. The Population in this study weremanufacturing 1 companies in the basic industry and chemical sectors listed on theIndonesia Stock Exchange for the period 2018-2019. The sampling technique in thisstudy was using purposive sampling method and obtained a sample of 33 companies inthe basic industry and chemical sector with a 2 year observation period and obtainedresearch data of 66 financial reports. The results showed that company size, companyage, and auditor reputation partially influence the timeliness of financial reportsubmission. While the profitability variable does no affect the timeliness of financialreport submission. The results of the f test show that the profitability, company size,company age, and auditor reputation simultaneously affect the timeliness of financialreport submission with a significance value less than 0.05.